OLLANTA HUMALA & THE PHANTOM OF CHÁVEZ IN 2006 PERUVIAN ELECTIONS - Luis León, Ángel Dámaso (Brazilian Journal of Latin American Studies, 2017)
In 2006, Peru faces an electoral process that would renew the head of their executive and legislative powers. In these elections, appeared external figures who want to win with his charisma as his main weapon. Among this group of regular contenders highlighted the military and nationalist Ollanta Humala. Humala represented in Peru the rise of the new left populist movements that had begun in 1999 with the arrival to power of Chavez in Venezuela. Identified as an element of rupturein this paper attempts to analyze the existing discursive conflict between supporters of the Bolivarian change and resistance.